The Histone Methyltransferase SETDB1 Modulates Survival of Spermatogonial Stem/Progenitor Cells Through NADPH Oxidase - Li, Xueliang; Chen, Xiaoxu; Liu, Yingdong; Zhang, Pengfei; Zheng, Yi; Zeng, Wenxian (Frontiers in Genetics, 2020)
SETDB1, a histone H3 lysine 9 (H3K9) methyltransferase, is indispensable in the meiosis and embryo development. Meanwhile, reactive oxygen species (ROS) play critical roles in SSC self-renewal. This study aimed to investigate SETDB1 whether associate with SSC homeostasis. We found that knockdown of SETDB1 led to increase reactive oxygen species (ROS) level through NADPH oxidase, and impaired cell proliferation. SETDB1 deficiency also activated ROS downstream signaling pathways including JNK and p38 MAPK, which possibly contributed to SSC apoptosis. Rescue experiments by scavenging ROS in SETDB1 knockdown cells demonstrated that ROS play a vital role in cell apoptosis induced by SETDB1 deficiency. In addition, we identified that SETDB1 regulated NADPH oxidase 4 (NOX4) and E2F1 in a H3K9me3 dependent manner. Therefore, this study uncovers the new roles of SETDB1 in mediating intracellular ROS homeostasis to maintain SSC survival.